Role of the type 3 cytokines IL-17 and IL-22 in modulating metabolic dysfunction-associated steatotic liver disease - Abdelnabi, Mohamed N.; Hassan, Ghada S.; Shoukry, Naglaa H. (Frontiers in Immunology, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD) comprises a spectrum of liver diseases that span simple steatosis, metabolic dysfunction-associated steatohepatitis (MASH) and fibrosis and may progress to cirrhosis and cancer. The pathogenesis of MASLD is multifactorial and is driven by environmental, genetic, metabolic and immune factors. This review will focus on the role of the type 3 cytokines IL-17 and IL-22 in MASLD pathogenesis and progression. IL-17 and IL-22 are produced by similar adaptive and innate immune cells such as Th17 and innate lymphoid cells, respectively. IL-17-related signaling is upregulated during MASLD resulting in increased chemokines and proinflammatory cytokines in the liver microenvironment, enhanced recruitment of myeloid cells and T cells leading to exacerbation of inflammation and liver disease progression. IL-17 may also act directly by activating hepatic stellate cells resulting in increased fibrosis. In contrast, IL-22 is a pleiotropic cytokine with a dominantly protective signature in MASLD and is currently being tested as a therapeutic strategy. IL-22 also exhibits beneficial metabolic effects and abrogates MASH-related inflammation and fibrosis development via inducing the production of anti-oxidants and anti-apoptotic factors. A sex-dependent effect has been attributed to both cytokines, most importantly to IL-22 in MASLD or related conditions. Altogether, IL-17 and IL-22 are key effectors in MASLD pathogenesis and progression. We will review the role of these two cytokines and cells that produce them in the development of MASLD, their interaction with host factors driving MASLD including sexual dimorphism, and their potential therapeutic benefits.